Environmental Awareness Followers Instagram Account @zerowaste.id_official Regrading the #HabiskanMakananmu Campaign - Tania Fathin Dwimaya; Tribuana Tungga Dewi (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2023)
This research begins with the amount of food waste that is increasing every year, to exceed the amount of plastic waste. Globally, food wasted gets 1.3 billion tonnes per year. In Indonesia, it is recorded that there will be 46.35 million tons of food waste in 2021, which if we calculate the wasted energy content, it should be able to provide decent food to 61-125 million people. This is an irony considering that the number of poor people in Indonesia is 26.50 million people. Therefore, the Zero Waste Indonesia Community Cares for the Environment launched a food waste- themed campaign, namely #HabiskanMakananmu. This campaign aims to invite people to finish the food they eat in order to reduce food waste. Based on the known background, the purpose of this study is to describe the level of environmental awareness of followers of the Instagram account @zerowaste.id_official related to the #HabiskanMakananmu campaign. This study uses a positivist paradigm with a quantitative descriptive approach. The unit of analysis in this study is individuals who are followers of the Instagram account @zerowaste.id_official with non- probability sampling technique and the method used is purposive sampling. This study uses one variable, namely environmental awareness related to the #HabiskanMakananmu campaign consisting of the dimensions of knowledge, attitude, and action. The result of the highest statement is on the dimension of knowledge, and the lowest statement is on the dimension of action, so based on the results it can be concluded that the environmental awareness of followers of the Instagram account @zerowaste.id_official is quite high in knowledge, but still low in attitudes and actions.